Evaluasi kualitas estetika tanaman lanskap jalan Ahmad Yani Kota Pontianak - Bahri, Hablul; Ruliyansyah, Agus; Pramulya, M. (Jurnal Arsitektur Lansekap, 2018)
Evaluation Aesthetic Quality of Plant Landscape Ahmad Yani Street Pontianak City. Ahmad Yani street is one of the streets located in downtown Pontianak. This road every day in passed by road users, be it a motorcycle or car and pedestrian. Structuring roads and plants continue to be done in accordance with its function.The purpose of this research is to evaluate to analyze the aesthetic quality of landscape plants and to formulate recommendations in improving or maintaining the quality of plant aesthetics. The method used in this research is survey, interview and questionnaire. Data analysis was processed through statistical questionnaires by means of SBE calculations by grouping based on the rating scale 1 to 10. The results stated assessment of aesthetic qualities with high grade SBE values is caused by neatly arranged plants and has a very attractive shape. The value of SBE with the medium category obtained from the form of an interesting plant but around the plant there is a pole or bulletin board that makes the scene less attractive. While the value of low category SBE is caused by plants that are not neatly arranged and the form of plants that are less interesting.